A Design Method of Virtual Folk Museum Roaming System Based on Visual Interaction Technology. (14th May 2022) - Li, Yifei
Abstract : The effective display of museums can greatly improve the attention of museums. The traditional museum display methods are old and old-fashioned. Aiming at the lack of vivid and immersive display in folklore museums, based on augmented reality technology and artificial intelligence, a virtual folklore museum roaming system based on visual interaction technology is proposed for 3D visualization of cultural heritage. The method applies the 6D pose estimation algorithm of objects to the display of museum objects. 6D pose estimation of objects refers to detecting objects present in an image and estimating their 3D position and orientation relative to the observer. In the field of augmented reality, 6D pose estimation is used to measure the pose of objects in the real environment and add virtual objects to it with the correct pose, thereby realizing augmented reality applications on the mobile side. The experimental results show that the 6D pose estimation method proposed in this paper has an accuracy rate of 93.3% and a running speed of 30 frames per second, which meets the needs of augmented reality applications and can be used in augmented reality museum display systems to provide them with vivid interactive content. Breaking through the time and space limitations of cultural heritage objects, it brings an immersive visiting experience to the audience.